FKBP Ligands—Where We Are and Where to Go? - Kolos, Jürgen M.; Voll, Andreas M.; Bauder, Michael; Hausch, Felix (Frontiers in Pharmacology, 2018)
In recent years, many members of the FK506-binding protein (FKBP) family were increasingly linked to various diseases. However, high-affinity ligands are scarce and selectivity issues between close homologs still need to be addressed. This review will give an overview of the most prominent ligands developed up to now and a perspective for future developments. More precisely, human FKBPs and correlated diseases will be discussed in the first part, followed by a discussion of microbial FKBPs in the context of anti-bacterial and anti-fungal therapeutics. The last section gives insights into high-affinity ligands as chemical tools and dimerizers.